Predicting the response of the deep-ocean microbiome to geochemical perturbations by hydrothermal vents - Reed, Daniel C; Breier, John A; Jiang, Houshuo; Anantharaman, Karthik; Klausmeier, Christopher A; Toner, Brandy M; Hancock, Cathrine; Speer, Kevin; Thurnherr, Andreas M; Dick, Gregory J (ISME JOURNAL, 2015)
Submarine hydrothermal vents perturb the deep-ocean microbiome by injecting reduced chemical species into the water column that act as an energy source for chemosynthetic organisms. These systems thus provide excellent natural laboratories for studying the response of microbial communities to shifts in marine geochemistry. The present study explores the processes that regulate coupled microbial-geochemical dynamics in hydrothermal plumes by means of a novel mathematical model, which combines thermodynamics, growth and reaction kinetics, and transport processes derived from a fluid dynamics model. Simulations of a plume located in the ABE vent field of the Lau basin were able to reproduce metagenomic observations well and demonstrated that the magnitude of primary production and rate of autotrophic growth are largely regulated by the energetics of metabolisms and the availability of electron donors, as opposed to kinetic parameters. Ambient seawater was the dominant source of microbes to the plume and sulphur oxidisers constituted almost 90{%} of the modelled community in the neutrally-buoyant plume. Data from drifters deployed in the region allowed the different time scales of metabolisms to be cast in a spatial context, which demonstrated spatial succession in the microbial community. While growth was shown to occur over distances of tens of kilometers, microbes persisted over hundreds of kilometers. Given that high-temperature hydrothermal systems are found less than 100 km apart on average, plumes may act as important vectors between different vent fields and other environments that are hospitable to similar organisms, such as oil spills and oxygen minimum zones.
Keywords: ROV Jason (Remotely Operated Vehicle)